Effect of Evolving Route of Hysterectomy on Cost: A 2001–2011 Nationwide Database Analysis [21]. (May 2015) - Borahay, Mostafa A.; Rodriguez, Ana Marina; Diken, Zaid; Sanford, Summer; Baxley, Sarah Emily; Kilic, Gokhan
Abstract : INTRODUCTION: The route of hysterectomy has been evolving over the past decade. With the current concern about health care spending, it is imperative to study the effect of this evolution on cost to find how to improve outcomes while containing cost. METHODS: We performed a retrospective analysis using the Healthcare Cost and Utilization Project Nationwide Inpatient Sample national database. We included all women who underwent hysterectomy from 2001 to 2011. For all cases, we extracted route of hysterectomy, hospital length of stay (LOS), and financial data. Data retrieval and analysis were done using SAS 9.3 software. RESULTS: A total of 1, 109, 090 hysterectomies were identified. Percentage of laparoscopic, robotic, open, and vaginal cases changed from 10%, 0%, 67%, and 22%, respectively, in 2001 to 24%, 13%, 45%, and 18%, respectively, in 2011. Average LOS changed from 1.82, 0, 3.15, and 2.07 days, respectively, in 2001 to 1.54, 1.83, 3.03, and 1.58 days, respectively, in 2011. Average charges for laparoscopic, robotic, open, and vaginal hysterectomy changed from 12, 981, not applicable, 12, 442, and 9, 561, respectively, in 2001 to 34, 916, 43, 879, 32, 736, and 25, 218, respectively, in 2011. The average charges for hysterectomy per year compared with vaginal hysterectomy (to account for inflation) stayed stable at 1.2–1.3. CONCLUSION: There is a trend for more use of the laparoscopic and robotic approaches, with shorter LOS. The increasing cost of open hysterectomy per case seems to be offset by a decreasing LOS for the laparoscopic and robotic approaches; therefore, the average cost of hysterectomy seems to be relatively stable.